Evaluation of Human Anti IgG Polyclonal Antibody Production Conjugated with Peroxidase in Egg Yolk - ABDOLMALEKI, Fahimeh (Iran J Public Health, 2019)
BACKGROUND: Egg yolk is a rich and accessible source of yolk immunoglobulin (Y immunoglobulin). Presently, polyclonal antibodies from mammalian sources are used for diagnosis. Antibody production from egg yolk gives a higher yield and turnover than that from lab animals, and invasive methods such as phlebotomy and causing stress to the animals are not required. Due to the issues regarding mammalian antibodies, we aimed to evaluate the human anti-IgG polyclonal antibody production conjugated with peroxidase in egg yolk. METHODS: Population of laying hens reared in Agriculture/Isfahan University of Technology were used in 2017. After immunizing hen against pure human IgG, specific IgY (yolk immunoglobulin) was purified from the yolk by sedimentation with polyethylene glycol (PEG6000). To assess the molecular weight and activity of the product, SDS-PAGE and ELISA-test were used, respectively. RESULTS: The complete molecular weight of IgY was 180 kDa and the molecular weight of its light and heavy chains were 27 and 67 kDa, respectively. CONCLUSION: Antihuman IgG IgY had a purity above 90%. The product of this study can be used to measure IgG class antibodies in order to diagnose different diseases.